232 Organisational impact of upcoming Huntington's disease treatments in Europe: resource gaps, access to care. Issue 6 (27th May 2022) - Pedrazzoli, Marco; Ponomareva, Marina; Moro, Mattia; Townson, Louisa; Mukelabai, Kopano; Levine, Aaron; Nordström, Anna-Lena; Guttman, Mark; Burgunder, Jean-Marc; Reilmann, Ralf
Abstract : Whilst no disease-modifying-therapies (DMTs) are currently available for Huntington's disease (HD), the investigational drugs most advanced in clinical development are administered intrathecally, requiring additional resources in HD clinics. We investigated the impact of upcoming DMTs for HD on healthcare systems and the implications of possible resource capacity gaps on access to care. The capacity to perform intrathecal drug administrations was assessed in 35 HD specialist centres from nine countries. Interviews with >170 healthcare professionals were performed and resources available in each HD centre were compared to the predicted amount of future resources that the estimated eligible patient population would need. Only 20% of participating HD teams currently have the required resources to perform intrathecal injec- tions: a skilled 'proceduralist', one or more nurses to assist in the procedure, and the appropriate space. When considering all resources available in the hospital, only 17% of HD-specialist clinics are estimated to have enough capacity to serve the eligible population. When simulating the additional referral-in of patients from non-HD-specialised clinics, only 6% of HD clinics have enough capacity. To ensure adequate care, capacity-constrained healthcare systems will need to plan adequately and ensure providers have sufficient training and resources to deliver new intrathecally administered DMTs. kopano.mukelabai@roche.com